Community participation in Indonesian sustainable tourism: A systematic review of models, impacts, and gaps - Muda, Florianus (Priviet Social Sciences Journal, 2025)
Community participation plays a vital role in sustainable tourism development by promoting social equity, environmental stewardship and local economic empowerment. However, systematic reviews that assess the diversity of participation models, their effectiveness across economic, social, and environmental dimensions, and their impacts on vulnerable groups in Indonesia are lacking. This study aimed to synthesize peer-reviewed literature to identify community participation models in sustainable tourism and examine their outcomes, best practices, implementation barriers, and research gaps. Using the PRISMA-based Systematic Literature Review (SLR) method, 54 articles published between 2018 and 2025 from reputable databases were analyzed thematically. The findings show that models such as Community-Based Tourism (CBT), multi-stakeholder collaboration, and local wisdom-based approaches contribute significantly to improving livelihoods, preserving cultural identity, and conserving ecosystems. Nonetheless, challenges persist, including symbolic participation, unequal benefit distribution, and the limited inclusion of women, youth, and indigenous communities. This study highlights the importance of hybrid approaches combining top-down policy with bottom-up initiatives, strengthening local institutions, and ensuring inclusive governance. Future research should incorporate social justice frameworks and conduct long-term impact evaluations to enhance the transformative potential of community participation in sustainable tourism governance in Indonesia.